1974
DOI: 10.1029/ja079i004p00619
|View full text |Cite
|
Sign up to set email alerts
|

Global characteristics in the diurnal variations of the thermospheric temperature and composition

Abstract: Global characteristics in the diurnal components of Ogo 6 neutral mass spectrometer measurements near 450 km are discussed qualitatively as well as quantitatively on the basis of a theoretical model. Observations and conclusions are summarized: (1) during equinox the temperature maximum occurs after 1600 LT at the equator and shifts toward 1500 LT at the poles, whereas the oxygen concentration at 450 km peaks about 1 h earlier (this observed phase difference is attributed primarily to wind‐induced diffusion, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 20 publications
(28 reference statements)
2
23
1
Order By: Relevance
“…On the other hand, Fuller‐Rowell et al [1997] suggested that this zonal wind transport mechanism seems to work in the wrong sense, given that the increase of zonal winds at the magnetic equator due to small zonal ion‐drag would carry hot dayside neutral parcels into the evening sector, creating a temperature bulge at the equator. This is not consistent with the OGO 6 measurements shown in Mayr et al [1974] in which neutral temperature/density after sunset did not show a peak at the magnetic equator. Another scenario, proposed by Fuller‐Rowell et al [1997], involves chemical heating.…”
Section: Introductioncontrasting
confidence: 95%
“…On the other hand, Fuller‐Rowell et al [1997] suggested that this zonal wind transport mechanism seems to work in the wrong sense, given that the increase of zonal winds at the magnetic equator due to small zonal ion‐drag would carry hot dayside neutral parcels into the evening sector, creating a temperature bulge at the equator. This is not consistent with the OGO 6 measurements shown in Mayr et al [1974] in which neutral temperature/density after sunset did not show a peak at the magnetic equator. Another scenario, proposed by Fuller‐Rowell et al [1997], involves chemical heating.…”
Section: Introductioncontrasting
confidence: 95%
“…Radar backscatter measurements at Arecibo (Harper, 1973;Cogger et al, 1974) have revealed occasional well deftned temperature maxima after midnight (~0200LT), where normally a fiat minimum is observed. Such a feature also appeared in the empirical OGO-6 model Mayr et al, 1974). More recently, in situ satellite measurements with the Neutral Atmospheric Temperature Experiment (Spencer et al, 1973) indicated pronounced temperature enhancements centered around midnight .…”
Section: Introductionmentioning
confidence: 76%
“…During solstices, the density crest in the summer hemisphere tends to occur 1–2 h earlier than that in the winter hemisphere [ Liu et al , 2007]. The model of Mayr et al [1974] predicted that the density crest in the winter hemisphere occurred 1–2 h earlier than that in the summer hemisphere. The reason for this discrepancy remains unclear.…”
Section: Discussionmentioning
confidence: 99%